MAIN CHARACTERISTICS AND STAGES OF CRITICAL THINKING - Mamadjanova, Nozima (Журнал иностранных языков и лингвистики, 2021)
This article provides a comprehensive overview of the concepts of criticism and stages for improvement of critical thinking. It describes the role of critical thinking in the learning process and definitions that foreign scientists give to the concept of critical thinking. In addition, there are examples from our study on the formation of critical thinking.